2021
DOI: 10.20944/preprints202112.0503.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological Control Strategies of Plant Pathogens

Abstract: Food security has become a major concern worldwide in recent years due to ever increasing population. Providing food for the growing billions without disturbing environmental balance is incessantly required in the current scenario. In view of this, sustainable modes of agricultural practices offer better promise and hence are gaining prominence recently. Moreover, these methods have taken precedence currently over chemical-based methods of pest restriction and pathogen control. Adoption of Biological Control i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…A similar phenomenon was observed in strawberries. The relative abundances of potential fungal pathogens including Fusarium (Frąc et al, 2018;Gwinn et al, 2022), Botrytis (Drobek et al, 2021;Pandit et al, 2022), Rhizoctonia (Frąc et al, 2018;Pandit et al, 2022), Dactylonectria (Su et al, 2022), Cadophora (Travadon et al, 2015), Neopestalotiopsis (Darapanit et al, 2021), and Colletotrichum (Drobek et al, 2021;Sangiorgio et al, 2022) were significantly higher in the rhizosphere soil and root endosphere samples of Akihime than those of F. nilgerrensis (Figure 5). At the same time, a variety of fungal pathogen taxa were detected in the samples of Akihime with higher relative abundances than F. nilgerrensis, especially in the root endosphere samples.…”
Section: Differences In Potential Pathogens and Beneficial Bacteria B...mentioning
confidence: 97%
See 1 more Smart Citation
“…A similar phenomenon was observed in strawberries. The relative abundances of potential fungal pathogens including Fusarium (Frąc et al, 2018;Gwinn et al, 2022), Botrytis (Drobek et al, 2021;Pandit et al, 2022), Rhizoctonia (Frąc et al, 2018;Pandit et al, 2022), Dactylonectria (Su et al, 2022), Cadophora (Travadon et al, 2015), Neopestalotiopsis (Darapanit et al, 2021), and Colletotrichum (Drobek et al, 2021;Sangiorgio et al, 2022) were significantly higher in the rhizosphere soil and root endosphere samples of Akihime than those of F. nilgerrensis (Figure 5). At the same time, a variety of fungal pathogen taxa were detected in the samples of Akihime with higher relative abundances than F. nilgerrensis, especially in the root endosphere samples.…”
Section: Differences In Potential Pathogens and Beneficial Bacteria B...mentioning
confidence: 97%
“…In addition, the Rhodococcus fascians taxa (APS), which can cause strawberry cauliflower disease, was detected in the rhizosphere soil and root endosphere samples of Akihime (data not shown). At the genus level, the relative abundances of potential fungal pathogens in the genera including Fusarium (Gwinn et al, 2022), Botrytis (Drobek et al, 2021), Rhizoctonia (Frąc et al, 2018;Pandit et al, 2022), Dactylonectria (Su et al, 2022), Neopestalotiopsis (Darapanit et al, 2021), Colletotrichum (Sangiorgio et al, 2022), and Cadophora (Travadon et al, 2015) were different between the F. nilgerrensis and Akihime samples (Figure 5). For the rhizosphere soil samples, the relative abundances of Fusarium, Botrytis, Neopestalotiopsis, Cadophora in F. nilgerrensis samples was significantly higher than those in Akihime samples (p < 0.05) (Figure 5D).…”
Section: Relative Abundances and Differences Of Pathogenic And Benefi...mentioning
confidence: 97%
“…In addition, the extensive use of agrochemicals molecules has led to the development of bacterial resistance, causing significant risks to the environment and human health (Ebele Mbachu et al, 2022). Consequently, providing food for the world's population without disrupting the environmental balance is becoming eminent (Pandit et al, 2022). It is highly recommended to provide sustainable solutions for agriculture (Jamiołkowska, 2020).…”
Section: Predatory Actinomycetota As An Eco-friendly and Promising To...mentioning
confidence: 99%
“…This view contradicts others who seek more sustainable agricultural production systems (Collinge et al, 2022;Pandit et al, 2022;Razo-Belman and Ozuna, 2023). Singh et al (2023) suggested that fungicide use has reached a plateau.…”
Section: Introductionmentioning
confidence: 96%